Inheritance of fruit colour and of shoot's pigmentation in the case of interspecific raspberry hybrids - Kollányi, L.; Kollányi, G. (International Journal of Horticultural Science, 2005)
In our research, fruit colour and the shoot's red pigmentation were evaluated in the hybrids of Rubus idaeus and Rubus parvifolius crossings. Y and Ys genes beside the T genes determine the fruit colour of interspecific hybrids, which is characteristic for raspberry. For the explanation of the significantly higher results of segregation then expected at the yellow fruit colour hybrids, we have supposed the presence of a second yellow gene (Y2). In the yellow colour, a lot of different shade colours can be identified from light yellow to the apricot colour. In the regulation of the production of yellow and red colour, several other genes can participate also. Identification of these genes would require more additional research. The C gene determines the shoot colour of raspberry and in the case of wild raspberries we have revealed the role of a dominant Pr gene. The Y and Pr genes are descended linked. The value of crossing over is approximately 15%. The anthocyanin production inhibitory effect of the Y gene extends only for fruit. At the shoots of yellow fruit plants, strong anthocyanin production was observed.